2003
DOI: 10.1111/j.0014-3820.2003.tb00582.x
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Models of Sympatric Speciation: Bush Versus Rice Versus Felsenstein

Abstract: In populations of phytophagous insects that use the host plant as a rendezvous for mating, divergence in host preference could lead to sympatric speciation. Speciation requires the elimination of "generalist" genotypes, that is, those with intermediate host preference. This could occur because such genotypes have an inherent fitness disadvantage, or because preference alleles become associated with alleles that are oppositely selected on the two hosts. Although the former mechanism has been shown to be plausib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
169
1
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(174 citation statements)
references
References 66 publications
(124 reference statements)
2
169
1
2
Order By: Relevance
“…The central results of this study (that extreme specialists outperform extreme generalists cognitively when, and only when, the fitness consequences of using a non-host resource are neutral or slightly positive) are important, following as they do a succession of theoretical models that essentially indicate increased suitability of non-host resources inhibits specialization and attendant speciation (19)(20)(21)(22)(23). Although some models have indicated that specialization can be promoted despite nonnegative fitness correlations of different resources (24)(25)(26), to our knowledge, this is the first study to have some degree of suitability of non-hosts as a necessary central component.…”
Section: Discussionmentioning
confidence: 99%
“…The central results of this study (that extreme specialists outperform extreme generalists cognitively when, and only when, the fitness consequences of using a non-host resource are neutral or slightly positive) are important, following as they do a succession of theoretical models that essentially indicate increased suitability of non-host resources inhibits specialization and attendant speciation (19)(20)(21)(22)(23). Although some models have indicated that specialization can be promoted despite nonnegative fitness correlations of different resources (24)(25)(26), to our knowledge, this is the first study to have some degree of suitability of non-hosts as a necessary central component.…”
Section: Discussionmentioning
confidence: 99%
“…Where local adaptation selects for habitat preferences (for example, Fry, 2003), it can have a more direct impact on the evolution of habitat isolation. The most widely accepted scenario for the evolution of pollinator isolation involves geographic separation of plant populations, divergence in floral traits then occurring as a result of disruptive selective pressures exerted by pollinators: for instance, plant populations experiencing completely different groups of pollinators or experiencing very different pollinator's preferences due to changes of the chemical environment (Coyne and Orr, 2004).…”
Section: Evolution Of Chemosensory Premating Isolationmentioning
confidence: 99%
“…parapatric or purely sympatric speciation. One mechanism likely to be important here is strong disruptive selection (owing to competition or discrete resources) that acts on traits also linked to assortative mating (Fry 2003;Gavrilets 2004;Bolnick & Fitzpatrick 2007). 'Context 3' is hybridization between groups following their secondary contact, which can sometimes cause the formation of a new hybrid species (Seehausen 2004;Mallet 2007).…”
Section: Introductionmentioning
confidence: 99%